Find the number of integer triples ( a , b , c ) with a ≤ b ≤ c and a < c , such that 2 8 8 a + b 2 c 2 = 2 8 8 b + c 2 a 2 = 2 8 8 c + a 2 b 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very nice solution. The argument in the a < b < c case is especially nice, almost no case-by-case analysis needed!
We have three equalities: 2 8 8 a + b 2 c 2 = 2 8 8 b + c 2 a 2 2 8 8 b + c 2 a 2 = 2 8 8 c + a 2 b 2 2 8 8 a + b 2 c 2 = 2 8 8 c + a 2 b 2 We can manipulate these equalities. 2 8 8 ( a − b ) + c 2 ( b 2 − a 2 ) = 0 2 8 8 ( a − b ) + c 2 ( b − a ) ( b + a ) = 0 And now, we divide by a − b , 2 8 8 = c 2 ( a + b ) or a = b ( 1 ) Similarly, we have: 2 8 8 = b 2 ( a + c ) or a = c ( 2 ) 2 8 8 = a 2 ( b + c ) or b = c ( 3 ) However, we are given c > a , so the left part of (2) is always true. We will focus on that one. We know that b 2 divides 288, and so we have 12 cases.
For each b 2 , we can try to find a , c such that b = a or b = c , since that eliminates an equation.
Say a = b c = b 2 2 8 8 − b Now, (1) and (2) are satisfied. (2) implies (3) since a = b , and so our assignments satisfy the system.
Similarly, b = c a = b 2 2 8 8 − b However, we must confirm that a < c in each solution.
b = 1 , a + c = 2 8 8 --> ( 1 , 1 , 2 8 7 ) is a solution ( a = b )
b = 2 , a + c = 7 2 --> ( 2 , 2 , 7 0 ) is a solution ( a = b )
b = 3 , a + c = 3 2 --> ( 3 , 3 , 2 9 ) is a solution ( a = b )
b = 4 , a + c = 1 8 --> ( 4 , 4 , 1 4 ) is a solution ( a = b )
b = 6 , a + c = 8 --> ( 2 , 6 , 6 ) is a solution ( b = c )
b = 1 2 , a + c = 2 --> ( − 1 0 , 1 2 , 1 2 ) is a solution ( b = c )
b = − 1 , a + c = 2 8 8 --> ( − 1 , − 1 , 2 8 9 ) is a solution ( a = b )
b = − 2 , a + c = 7 2 --> ( − 2 , − 2 , 7 4 ) is a solution ( a = b )
b = − 3 , a + c = 3 2 --> ( − 3 , − 3 , 3 5 ) is a solution ( a = b )
b = − 4 , a + c = 1 8 --> ( − 4 , − 4 , 2 2 ) is a solution ( a = b )
b = − 6 , a + c = 8 --> ( − 6 , − 6 , 1 4 ) is a solution ( a = b )
b = − 1 2 , a + c = 2 --> ( − 1 2 , − 1 2 , 1 4 ) is a solution ( a = b )
So far, we have 12 solutions. Now, if more solutions exist, then a = b = c . Therefore, a 2 ( b + c ) = b 2 ( a + c ) = c 2 ( a + b ) = 2 8 8 If this works, a 2 ∣ 2 8 8 , b 2 ∣ 2 8 8 , and c 2 ∣ 2 8 8 . Also, b 2 ( a + c ) = 2 8 8 . This means that a , b , c > 3 , since if one is below, then the sum of the other two must be at least 3 2 > 1 2 + 1 2 = 2 4 . Now, we have 6 possible values, and it is easy to confirm that the only other solution is ( − 4 , 6 , 1 2 ) .
The answer is 1 3 .
Fine solution! There is a little misprint at the end: the sentence "This means that a , b , c > 3 " should be "This means that ∣ a ∣ , ∣ b ∣ , ∣ c ∣ > 3 ".
Let's drop the condition a ≤ b ≤ c first and consider all solutions where not all a, b, c are equal.
Consider the case where two of the variables are equal, i.e. a=b without loss of generality. Then:
2 8 8 a + b 2 c 2 = 2 8 8 c + a 2 b 2 ⟹ 2 8 8 ( a − c ) = b 2 ( a 2 − c 2 ) = b 2 ( a − c ) ( a + c )
and since a, b, c are not all equal, we have a = c so 2 8 8 = b 2 ( a + c ) = b 2 ( b + c ) . Thus, the set of solutions corresponds to each integer b such that b 2 ∣ 2 8 8 , since we can just let a=b and c = b 2 2 8 8 − c . This gives 12 solutions:
b = ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 .
The remaining case is where a, b, c are all distinct. Following the above reasoning, we get:
2 8 8 = a 2 ( b + c ) = b 2 ( a + c ) = c 2 ( a + b )
so a , b , c = ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 . Since − 2 4 ≤ b + c ≤ 2 4 , we can't have a = ± 1 , ± 2 , ± 3 since that would imply b + c = 2 8 8 , 7 2 , 3 2 respectively. Thus, a , b , c = ± 4 , ± 6 , ± 1 2 .
Consider the case where a=4. This gives b + c = 2 8 8 / 1 6 = 1 8 so we must have (b,c) = (6,12) or (12,6) which contradicts b 2 ( a + c ) = 2 8 8 . The case a=-4 also gives b+c=18, but here, this works so we get a solution of (-4, 6, 12).
Excluding the case of -4 and +4, we're left with a , b , c = ± 6 , ± 1 2 . This is clearly impossible since a, b, c are all multiples of 6 and that would give 2 1 6 ∣ b 2 ( a + c ) .
Conclusion: 13 solutions, 12 of which corresponds to a=b or b=c and the final one is (-4, 6, 12).
Nicely done!
Since a < c , we have 2 8 8 ( a − c ) = b 2 ( a 2 − c 2 ) ⟹ 2 8 8 = b 2 ( a + c ) .
If a < b < c , we similarly have 2 8 8 = c 2 ( a + b ) and 2 8 8 = a 2 ( b + c ) > a 2 ( 2 a ) = 2 a 3 . Since a 2 ∣ 2 8 8 , it follows that a ≤ 4 . Then b + c = a 2 2 8 8 ≥ 1 6 2 8 8 = 1 8 . However, note that b , c must equal one of the folllowing: ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 with b < c . Thus, the only way to satisfy b + c ≥ 1 8 is when a = ± 4 , b = 6 , c = 1 2 . Checking, only a = − 4 , b = 6 , c = 1 2 works.
If a = b < c , 2 8 8 = b 2 ( a + c ) reduces to 2 8 8 = a 2 ( a + c ) > a 2 ( 2 a ) = 2 a 3 , so as before, a ≤ 4 . Thus, out of the possible values: ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 , only a = ± 1 , ± 2 , ± 3 , ± 4 , − 6 , − 1 2 work, for a total of 1 0 solutions.
If a < b = c , we have 2 8 8 = c 2 ( a + c ) < c 2 ( 2 c ) = 2 c 3 , so c ≥ 6 . Again, out of the possible values: ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 , only c = 6 , 1 2 work, for a total of 2 solutions.
As a result, there are 1 + 1 0 + 2 = 1 3 solutions.
There is a little mistake here. Because a may be negative, the sentence "Then b + c = a 2 2 8 8 ≥ 1 6 2 8 8 = 1 8 ." is not justified. Indeed, if a < 0 , it can be less than − 4 .
Note that ( 0 , 0 , 0 ) is not a solution since a < c . Since a < c , then if any two variables are equal we can either have a = b or b = c . But, before that we will try to find integer solutions such that a , b , c are distinct.
Solving the given equations will give us the following system of equations:
a 2 ( b + c ) = 2 8 8
b 2 ( c + a ) = 2 8 8
c 2 ( a + b ) = 2 8 8 Now we note that since a , b , c are integers, then a 2 , b 2 , c 2 have to be square numbers that divide 2 8 8 Also, ( b + c ) , ( a + b ) , ( a + c ) ∣ 2 8 8 [Divides]. So, a , b , c ∈ ( ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 ) . Clearly, − 1 2 ≤ a , b , c ≤ 1 2 and, 0 ≤ ( a + c ) , ( b + c ) , ( a + b ) ≤ 2 4 [Since they can only be positive].
So, a , b , c ∈ ± 4 , ± 6 , ± 1 2 Suppose, if a = 4 then since the integers need to be distinct and our conditions satisfied the only possible triple is ( 4 , 6 , 1 2 ) . Since 4 + 6 = 1 0 which does not divide 2 8 8 , this triple is not a solution.
If, a = − 4 then b = 6 and it can’t equal 4 or 1 2 . It can’t equal 4 because then we have c = 0 which is not possible. It can’t equal 1 2 because we look for distinct triples. So, we have ( − 4 , 6 , 1 2 ) as a possible candidate. We check that ( − 4 , 6 , 1 2 ) does, indeed, satisfy the given equations. Now if a = − 6 , we can have b = 4 and, c = 1 2 . Note that a + b = − 2 , but since c 2 is obviously a positive factor of 2 8 8 so must be a + b . So, we reject this case as well. An analogous argument for a = − 1 2 tell us that there can be no solutions.
Now, when a = b :
Note that in this case \(b \neq c\( Our original equations reduce to:
\(288b + b^2 c^2 = 288b + c^2 b^2 = 288c + b^4 \)
⇒ 2 8 8 b + c 2 b 2 = 2 8 8 c + b 4 2 8 8 ( b − c ) = b 2 ( b 2 − c 2 ) 2 8 8 = b 2 ( b + c ) [Since b = c ] b ∈ ( ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 )
Clearly there will exist integer solutions to c for all the above b . But, we have to consider the order such that a < c . But, we see that if we ignore the condition we have 12 triples such that a = b .
For example if there exists such triple in the above triples such that a > c , then we can simply exchange the value of a with c and our condition becomes b = c .We can do this, since we see that if we replace the relative position a , b , c in the original equations, the equations remain unchanged.
Let 288 + b^2 c^2 = 288b + c^2 a^2 = 288c + a^2 b^2=k\ for some integer \(k \neq 0
2 8 8 ( a + b + c ) + b 2 c 2 + c 2 a 2 + a 2 b 2 − 3 k = 0
Let f ( a , b , c ) = 2 8 8 ( a + b + c ) + b 2 c 2 + c 2 a 2 + a 2 b 2 − 3 k
Clearly this is the same as f ( a , c , b ) , f ( c , a , b ) , f ( c , b , a ) . This concludes our proof that there are 12 solutions to the case when either a = b or b = c [ a = c ] We don’t need to check separately for b = c since we have already counted those triples. Total number of solutions is 1 3
divides in 3 case case 1 a=b<c equation is a^2(a+c)=288=2^5x3^2=2x(2^2)^2x3^2 because in LHS a^2, a=+-1,+-2,+-3,+-4,+-6,+-12 a=b=-1, c=289 a=b=1, c=287 a=b=-2, c=74 a=b=2, c=70 a=b=-3, c=35 a=b=3, c=29 a=b=-4, c=22 a=b=4, c=14 a=b=-6, c=14 a=b=6, c=2 (a>c) (not solution) a=b=-12, c=14 a=b=12, c=-10, notsolution so there are 10 solution for first case Case 2 a<b=c the equation is b^2(a+b)=288 similiarly only b=c=12, a=-10 and b=c=6, a=2 Case 3 a<b<c only a=-4,b=6, c=12
So the total solution is 13
Let's drop the condition a≤b≤c first and consider all solutions where not all a, b, c are equal.Consider the case where two of the variables are equal, i.e. a=b without loss of generality. Then:288a+b2c2=288c+a2b2⟹288(a−c)=b2(a2−c2)=b2(a−c)(a+c)and since a, b, c are not all equal, we have a≠c so 288=b2(a+c)=b2(b+c). Thus, the set of solutions corresponds to each integer b such that b2|288, since we can just let a=b and c=288b2−c. This gives 12 solutions:b=±1,±2,±3,±4,±6,±12.The remaining case is where a, b, c are all distinct. Following the above reasoning, we get:288=a2(b+c)=b2(a+c)=c2(a+b)so a,b,c=±1,±2,±3,±4,±6,±12. Since −24≤b+c≤24, we can't have a=±1,±2,±3 since that would imply b+c=288,72,32 respectively. Thus, a,b,c=±4,±6,±12.Consider the case where a=4. This gives b+c=288/16=18 so we must have (b,c) = (6,12) or (12,6) which contradicts b2(a+c)=288. The case a=-4 also gives b+c=18, but here, this works so we get a solution of (-4, 6, 12).Excluding the case of -4 and +4, we're left with a,b,c=±6,±12. This is clearly impossible since a, b, c are all multiples of 6 and that would give 216|b2(a+c).Conclusion: 13 solutions, 12 of which corresponds to a=b or b=c and the final one is (-4, 6, 12).
Did you really copy-paste C.L.s solution?
=0 =!!!
We split the problem into three cases:
Case 1 , a<b<c : In this case, we know that none of a − b , b − c , c − a are 0 , and so we can divide through by them. 2 8 8 a + b 2 c 2 = 2 8 8 b + c 2 a 2 → 2 8 8 ( a − b ) = c 2 ( a 2 − b 2 ) → 2 8 8 = c 2 ( a + b ) , and through similar algebra, we arrive at 2 8 8 = a 2 ( b + c ) = b 2 ( c + a ) = c 2 ( a + b ) . Because a , b , c ∈ Z , a 2 , b 2 , c 2 ∣ 2 8 8 (otherwise, the sum of two integers is not an integer, which is impossible). Thus, a 2 , b 2 , c 2 ∣ 3 2 ⋅ 2 5 → a , b , c ∈ { ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 } . We proceed to test each possible value of a 2 by plugging it into the equation 2 8 8 = a 2 ( b + c ) : since b + c ≤ 1 8 (remember, b < c ), a 2 ≥ 1 6 → a ∈ { ± 4 , ± 6 , ± 1 2 } . We can verify that a = − 4 yields ( a , b , c ) = ( − 4 , 6 , 1 2 ) , which also works in the other two equalities. a = 6 , 1 2 yield no solutions because a < b < c , and then the solutions we get from a = − 6 , − 1 2 do not work in the other equalities. Therefore, this case yields only the ordered triple ( − 4 , 6 , 1 2 ) .
Case 2 , a = b < c : In this case, we can substitute all the b 's with a 's to get the equality 2 8 8 a + a 2 c 2 = 2 8 8 c + a 2 a 2 = 2 8 8 c + a 4 → 2 8 8 ( a − c ) = a 2 ( a 2 − c 2 ) = a 2 ( a + c ) ( a − c ) . Because a < c , we can divide through by a − c to get 2 8 8 = a 2 ( a + c ) → a 2 2 8 8 − a 3 = c . Clearly, a 2 ∣ a 3 , so we need a 2 ∣ 2 8 8 , and we already know that the values of a that satisfy this are ± 1 , ± 2 , ± 3 , ± 4 , ± 6 , ± 1 2 . This gives us 1 2 ordered triples of the form ( a , a , a 2 2 8 8 − a 3 ) . However, we must remember that a < c → a < a 2 2 8 8 − a 3 → 2 a 3 < 2 8 8 → a < 3 1 4 4 . Thus, we have 1 0 ordered triples in this case, because we must remove ( 6 , 6 , 3 ) and ( 1 2 , 1 2 , − 1 0 ) .
Case 3 , a < b = c : In this case, we use manipulations very similar to those in Case 2 to get that 2 8 8 = c 2 ( c + a ) and a < c . Notice that replacing the a 's with c 's and vice-versa yields 2 8 8 = a 2 ( a + c ) and a > c , which gives precisely the two solutions we eliminated from Case 2 with just the value for a switched with the value for c . Thus, we get two solutions in this case, namely ( a , b , c ) = ( 3 , 6 , 6 ) , ( − 1 0 , 1 2 , 1 2 ) .
We can verify trivially that there are no repeats in these three cases because in each case, the behavior of b is different. In each of Case 2's solutions, for example, b = a , and so none of those solutions can also be a solution in Case 1 or Case 3.
Therefore, we have a total of 1 + 1 0 + 2 = 1 3 ordered triples of integers ( a , b , c ) which satisfy the given conditions.
Let's consider the cases of a < b and a ≤ b separately. If a < b then none of a − b , a − c or b − c are zero so we can take the differences between each of the three equalities in the question and divide through by the above factors to obtain a 2 ( b + c ) = 2 8 8 , b 2 ( a + c ) = 2 8 8 and c 2 ( a + b ) = 2 8 8 . We therefore have a 2 , b 2 , c 2 ∣ 2 8 8 = 2 5 × 3 2 so a , b , c ∣ 2 2 × 3 = 1 2 . If ∣ a ∣ ≤ 3 then there is no way that b + c = 2 8 8 / a 2 ≥ 3 2 if b , c ∣ 1 2 so we have a ∈ { − 1 2 , − 6 , − 4 , 4 , 6 , 1 2 } . Since a < b < c , the value of a cannot be 6 or 12 so this reduces the options to a ∈ { − 1 2 , − 6 , − 4 , 4 } . Also since 0 < a + b we cannot have a ∈ { − 1 2 , − 6 } . So we need only examine a = ± 4 . We need b + c = 1 8 and the only possibility for this is b = 6 and c = 1 2 , and we find that the only valid solution here is ( a , b , c ) = ( − 4 , 6 , 1 2 ) .
Now we deal with the case a = b . We now only have one equality to examine and this reduces to a 2 ( a + c ) = 2 8 8 . By the same logic as before we have a ∣ 1 2 however there is no such condition on c here, thus we can allow a to take any of the 12 divisors of 12, and setting c = 2 8 8 / a 2 − a does the job. So we have solutions ( − 4 , 6 , 1 2 ) and ( d , d , 2 8 8 / d 2 − d ) for d ∣ 1 2 . A total of 1 + 1 2 = 1 3 solutions.
Problem Loading...
Note Loading...
Set Loading...
We have 2 8 8 a + b 2 c 2 = 2 8 8 c + a 2 b 2 ⇒ 2 8 8 ( c − a ) = b 2 ( c − a ) ( c + a ) and since that c > a we have c − a > 0 and by the last equal,we can conclude that
( ∗ ) 2 8 8 = b 2 ( a + c )
Since that 2 8 8 = 2 5 3 2 and b 2 ∣ 2 8 8 , we have b = 2 x 3 y , where x ≤ 2 , y ≤ 1 ⇒ b ∣ 1 2 .
Now, we are going divide in three cases:
( 1 ) b = c
By ( ∗ ) , we have a < c ⇒ a + c < 2 c ⇒ 2 8 8 = b 2 ( a + c ) < 2 b 2 c = 2 b 3
and soo b > 5 . How b ∣ 1 2 , then b = 6 , 1 2 .
If b = c = 6 , b = c = 1 2 , by the ( ∗ ) we have a = 2 , − 1 0 , respectively, and in both cases, we have a < c , a ≤ b ≤ c . Solutions ( a , b , c ) = ( 2 , 6 , 6 ) ; ( − 1 0 , 1 2 , 1 2 ) .
( 2 ) b = a
We have a < c ⇒ 2 a < a + c ⇒ 2 b 3 = 2 a b 2 < b 2 ( a + c ) = 2 8 8 , where b < 5 and b ∣ 1 2 , then ( ∗ ∗ ) b = − 1 2 , − 6 , − 4 , − 3 , − 2 , − 1 , 1 , 2 , 3 , 4 .
If b < 0 , we have 0 < 2 8 8 = b 2 ( a + c ) = b 2 ( b + c ) , b 2 > 0 , where b + c > 0 ⇒ c > − b > 0 > b = a , and soo every negative value for b in ( ∗ ∗ ) generates a solution. Explicity, we have c = 2 ( b 1 2 ) 2 − b
So we have 6 solutions.
By test for error, we conclude that b = 1 , 2 , 3 , 4 generates solutions which satisfy a ≤ b ≤ c , a < c and we have 4 new solutions.
( 3 ) a < b < c
By a similar simplification to ( ∗ ) we have ( ∗ ∗ ∗ ) a 2 ( b + c ) = b 2 ( a + c ) = c 2 ( a + b ) = 2 8 8 .
By the same argument, we have c ∣ 1 2 and a + b < 2 c ⇒ 2 8 8 = c 2 ( a + b ) < 2 c 3 , c > 5 and we have c = 6 , 1 2 .
If c = 6 , ( ∗ ∗ ∗ ) give us a + b = 6 2 2 8 8 = 8 , a 2 b + 6 a 2 = a b 2 + 6 b 2 ⇒ a b = − 6 ( a + b ) = − 4 8 and we have a = − 4 , b = 1 2 since that a < b . It's a contradiction with b < c .
If c = 1 2 ( ∗ ∗ ∗ ) give us a + b = 1 2 2 2 8 8 = 2 , a 2 b + 1 2 a 2 = a b 2 + 1 2 b 2 ⇒ a b = − 1 2 ( a + b ) = − 2 4 and we have a = − 4 , b = 6 since that a < b . Actually, ( a , b , c ) = ( − 4 , 6 , 1 2 ) is a solution.
So we have 2 + 6 + 4 + 0 + 1 = 1 3 solutions.